Sharia Compliance Analysis of Indonesia’s National Health Insurance (BPJS Kesehatan): A Hybrid Model Between Takaful Principles and State Social Insurance - Cholis Waidi Salaman (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study analyzes the Sharia compliance of BPJS Kesehatan as Indonesia’s national social health insurance system by examining its contractual structure, contribution mechanism, fund management, penalty system, and participation status. The research is motivated by the need to evaluate whether state-based social insurance aligns with Islamic insurance (takaful) principles within fiqh muamalat. A qualitative case study approach was applied using interviews, field observations, focus group discussions, and document analysis. Data were analyzed using inductive and deductive methods based on Islamic jurisprudence and social insurance theory, supported by comparative perspectives from Indonesian Islamic institutions. Findings show that BPJS Kesehatan is structurally aligned with the Islamic principle of tabarruʿ through collective risk-sharing and mutual assistance (taʿāwun). However, it does not fully comply with Islamic insurance contracts such as wakālah bi al-ujrah due to its statutory nature and lack of formal Sharia governance. In addition, investment of funds in non-Sharia-compliant instruments and the contested nature of late payment penalties indicate partial Sharia non-compliance at the operational level. Despite these issues, participation is considered permissible (mubāḥ) based on public necessity and welfare considerations. The study concludes that BPJS Kesehatan is a hybrid social insurance system with partial Sharia alignment, requiring governance reform in investment management and contractual standardization to achieve full compliance.